Micmac Numerals: An Etymological Study - Dawe-Sheppard, Audrey (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
This paper presents an etymological explanation of the Micmac numerals. The Micmac numerals are examined to discern whether they are reflexes of the possible reconstructions labeled by Siebert as the quinary system, the decimal system and the descriptive system. It will be shown that Micmac shows a blending of the three systems. Examples from other Algonkian languages (including both Eastern and Central) will be examined to show that other languages, like Micmac, also have a blending of the systems. The numerals from 1 to 10 will be the major focus; but other numerals which display a noteworthy etymology will be presented and examined.